Conversational Implicature in Frozen 1:: A Pragmatic Approach - A'maliyah, Nazila; Eva Kavka Mi’rajiah; Tatu Siti Rohbiah (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to examine the types and meanings of conversational implicatures in the film Frozen 1 using a pragmatic approach. Conversational implicatures refer to implied meanings that are interpreted based on the context of utterances. This study refers to Grice's theory of cooperation principles and conversational maxims. The method used is qualitative descriptive with content analysis techniques. The data, consisting of dialogues between characters, were categorized into conventional and non-conventional implicatures. The results show that implicatures in this film appear through violations of maxims such as quantity, quality, relevance, and manner. The use of implicatures aims to convey hidden messages such as sarcasm, subtle rejection, criticism, and polite expressions. These findings prove that animated films are not only a means of entertainment but also contain valuable linguistic elements. The analysis of implicatures, which includes forms of sarcasm, subtle rejection, criticism, and polite expressions, shows that animated films have a broader role than mere entertainment; they contain important pragmatic values. therefore, this study contributes to the development of pragmatic studies while offering the potential for utilizing animated films as a language learning medium to sharpen the ability to understand implied meanings, with a recommendation that future research examine the application of implicature in various film genres or other media to enrich understanding of linguistic diversity.